Composite fiber and fabric including the same
The composite fiber, utilizing aminolic polyamide resin and crystalline poly α-olefin with carbon black, addresses scattering and dyeability issues, providing improved temperature control and dyeing capabilities for clothing.
Patent Information
- Application Number
- JP2024194777
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-28
AI Technical Summary
Existing temperature control fibers face issues such as microcapsule scattering, reduced performance, poor laundry durability, difficulty in manufacturing with paraffin wax compositions, and poor dyeability with crystalline poly α-olefin and polypropylene, leading to inadequate temperature control and dyeing capabilities.
A composite fiber is developed using aminolic polyamide resin with a terminal amino group amount of 60 MEQ/kg or more, combined with crystalline poly α-olefin and carbon black, forming a core sheath structure to enhance dyeability and temperature control performance.
The composite fiber achieves improved dyeability and excellent temperature control performance, suitable for clothing applications, with enhanced durability and stability during environmental temperature changes.
Smart Images

Figure 2025014069000001 
Figure 2025014069000002 
Figure 2025014069000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a conjugate fiber having excellent temperature regulating properties and a fabric made thereof. [Background technology]
[0002] Various fibers having a temperature regulating function (hereinafter, sometimes referred to as temperature regulating yarns) have been proposed in the past. For example, Patent Document 1 proposes the use of a heat storage material in which a substance having a melting point near room temperature is encapsulated in microcapsules. Such microcapsules can be used as temperature regulating yarns by attaching them to fibers or mixing them into fibers. Furthermore, Patent Documents 2 and 3 propose techniques relating to composite fibers that use a paraffin wax composition as a core component and have excellent temperature regulating properties. Furthermore, Patent Document 4 proposes a core-sheath type composite fiber that uses a resin composition containing crystalline poly-α-olefin and polypropylene as the core component and has excellent temperature regulating properties. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 64-85374 [Patent Document 2] Japanese Patent Application Publication No. 8-311716 [Patent Document 3] JP 2004-11032 A [Patent Document 4] JP 2017-119939 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, in the case of attaching microcapsules to a base material such as a fiber or fabric as in Patent Document 1, there are problems such as the microcapsules being scattered and the entire fiber not being able to fully exhibit its performance, and problems such as the performance decreasing with use and poor washing durability. Also, when microcapsules are mixed into fibers, there is a problem that the microcapsules are destroyed when kneaded into the fiber-forming resin or melted during spinning. As described in Patent Documents 2 and 3, composite fibers using a paraffin wax composition as a core component as a phase change material have problems such as difficulties in fiber production due to the paraffin wax scattering due to heat or the like during fiber production, and the obtained fibers do not exhibit excellent temperature regulating performance. The crystalline poly-α-olefin and polypropylene contained in the above-mentioned fiber described in Patent Document 4 are extremely poor in reactivity with other compounds, and therefore are very difficult to dye with acid dyes. The above-mentioned fiber described in Patent Document 4 is composed of approximately 50% crystalline poly-α-olefin and polypropylene, and therefore has a problem of poor dyeability and inability to be dyed deeply compared to general polyester-based and polyamide-based fibers used for clothing.
[0005] An object of the present invention is to solve the above problems and to obtain fibers and fabrics having good dyeability, spinnability and excellent temperature control properties. [Means for solving the problem]
[0006] It is common to use polyamide resins (hereinafter sometimes simply referred to as polyamide resins) in which the polymerization reaction has been terminated by reacting the terminal amino groups with methyl carboxylic acid or the like. However, we have focused on polyamide resins (hereinafter sometimes referred to as amino-rich polyamide resins) in which the polymerization reaction has been terminated without reacting the terminal amino groups with acid, and have found that the use of amino-rich polyamide resins improves the dyeability of conventional temperature regulating yarns. Furthermore, when dyeing a temperature regulating yarn in a darker color, the inventors have found that a temperature regulating yarn that can be dyed darker can be obtained by using a mixed resin in which an olefin resin-based masterbatch containing carbon black is kneaded into crystalline poly-alpha-olefin and an olefin resin other than crystalline poly-alpha-olefin (hereinafter simply referred to as olefin resin) to produce a dyed temperature regulating yarn. That is, the present invention is a composite fiber containing a crystalline poly-α-olefin having a structural unit constituted by ethylene and a structural unit represented by formula 1, and a polyamide resin having a terminal amino group amount of 60 meq / kg or more. [ka] (In the formula, the side chain portion R is a linear alkyl group having 9 to 30 carbon atoms.) The above-mentioned composite fiber is preferably a core-sheath type composite fiber containing carbon black in a resin composition containing the above-mentioned crystalline poly-α-olefin. The composite fiber preferably has a crystalline poly-α-olefin content of 5% by mass or more and 25% by mass or less, and a polyamide resin content of 60 meq / kg or more of terminal amino groups of 40% by mass or more and 70% by mass or less. In the above composite fiber, the crystalline poly-α-olefin preferably has a melting point of 20° C. or more and 50° C. or less, a freezing point of 15° C. or more and 45° C. or less, a heat of fusion (ΔHm) of 60 J / g or more and 100 J / g or less, and a heat of solidification (ΔHc) of 60 J / g or more and 100 J / g or less. The above-mentioned composite fiber is preferably a core-sheath type composite fiber in which the resin composition containing crystalline poly-α-olefin forms the core, and the polyamide resin having a terminal amino group amount of 60 meq / kg or more forms the sheath. Furthermore, the present invention is also directed to a fabric containing the above-mentioned composite fiber. Effect of the Invention
[0007] According to the present invention, a temperature regulating yarn using an amino-rich polyamide resin can be dyed darker than a temperature regulating yarn using only a polyamide resin, and by further kneading in carbon black, a temperature regulating yarn of an even darker color can be obtained. In addition, when considering wearing the material as clothing, the material has excellent temperature regulating performance against changes in environmental temperature that occur in summer and winter, such as when moving from indoors to outdoors, and therefore it is possible to provide a fiber and a fabric thereof that have good dyeability and temperature regulating properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention is a composite fiber comprising a crystalline poly-α-olefin having a structural unit constituted by ethylene and a structural unit represented by formula 1, and a polyamide resin having a terminal amino group amount of 60 or more meq / kg or more.
[0009] [ka] (In the formula, the side chain portion R is a linear alkyl group having 9 to 30 carbon atoms.)
[0010] The melting point of the crystalline poly-α-olefin is 20° C. or higher and 50° C. or lower, and more preferably 25° C. or higher and 45° C. or lower, in order to provide good temperature control performance. In addition, the freezing point of the crystalline poly-α-olefin is preferably 15° C. or higher and 45° C. or lower, and more preferably 17° C. or higher and 40° C. or lower, in order to provide good temperature control performance. In addition, the melting point of the crystalline poly-α-olefin is preferably 3° C. or more higher than the freezing point.
[0011] In the crystalline polyα-olefin used in the present invention, R in formula 1 is a linear alkyl group. The melting point and freezing point of the crystalline polyα-olefin are determined by the carbon number of the linear alkyl group. The linear alkyl group preferably has 9 to 30 carbon atoms, more preferably has 14 to 24 carbon atoms, and even more preferably has 16 to 22 carbon atoms.
[0012] The fusion heat (ΔHm) of the crystalline poly-α-olefin is preferably 60 J / g or more and 100 J / g or less, and the solidification heat (ΔHc) is preferably 60 J / g or more and 100 J / g or less. By setting it in this range, excellent temperature control performance can be obtained when it is fiberized.
[0013] When the crystalline polyα-olefin has a structure in which many monomer units in which R in formula 1 is a linear alkyl chain are consecutive, the structural unit is broken down, so it is preferable that the crystalline polyα-olefin contains a large amount of monomer units composed of ethylene. When the total amount of monomer units constituting the crystalline polyα-olefin is taken as 100 mol%, the content of monomer units composed of ethylene is preferably 50 mol% or more, more preferably 80 mol% or more. In addition, from the viewpoint of improving the heat storage performance, it is more preferably 95 mol% or less, and even more preferably 90 mol% or less.
[0014] A suitable method for producing crystalline polyα-olefins includes a method of polymerizing one or more monomers selected from ethylene and α-olefins having 9 to 30 carbon atoms. A suitable catalyst to be used is a metallocene catalyst. In particular, the catalyst is preferably one using a transition metal compound in which the ligand forms a crosslinked structure via a crosslinking group, and a metallocene catalyst obtained by combining a transition metal compound that forms a crosslinked structure via two crosslinking groups with a cocatalyst is preferred.
[0015] Examples of α-olefins having 9 or more and 30 or less carbon atoms include 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nanodecene, 1-eicosene, 1-heneicosene, 1-docosene, 1-tricosene, 1-tetracosene, 1-pentacosene, 1-hexacosene, 1-heptacosene, 1-octacosene, 1-nanocosene, and 1-triacontene.
[0016] The polymerization temperature is usually 0°C or higher and 200°C or lower, preferably 20°C or higher and 150°C or lower, and more preferably 40°C or higher and 100°C or lower. The polymerization time is usually 5 minutes or more and 10 minutes or less, and the reaction pressure is preferably normal pressure or more and 20 MPa or less, more preferably normal pressure or more and 10 MPa or less.
[0017] When carrying out the polymerization, it is preferable to carry out the polymerization without a solvent, but a solvent can also be used. In that case, for example, aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene, alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclohexane, aliphatic hydrocarbons such as pentane, hexane, heptane, and octane, and halogenated hydrocarbons such as chloroform and dichloromethane can be used. These solvents can be used alone or in combination of two or more. Also, a monomer such as an α-olefin can be used as a solvent. The catalyst is used in an amount of 0.01 to 20 μmol, preferably 0.1 to 15 μmol, more preferably 0.5 to 10 μmol, calculated as an organometallic complex, per 100 g of raw monomer.
[0018] The resin composition containing the crystalline poly-α-olefin in the present invention may further contain an olefin resin other than the crystalline poly-α-olefin.
[0019] In a resin composition containing a crystalline poly-α-olefin and an olefin resin (hereinafter sometimes referred to as resin composition (A)), the crystalline poly-α-olefin is preferably 15% by mass or more and 40% by mass or less relative to the resin composition (A). If it is 15% by mass or more, excellent temperature control performance is easily exhibited, and if it is 40% by mass or less, the resin composition can be stably produced. More preferably, it is 15% by mass or more and 30% by mass or less, and even more preferably, it is 15% by mass or more and 25% by mass or less. The olefin resin is preferably 60% by mass or more and 85% by mass or less, more preferably 70% by mass or more and 85% by mass or less, and even more preferably 75% by mass or more and 85% by mass or less, based on the resin composition (A).
[0020] By using amino-rich polyamide resin, it is possible to dye the temperature regulating yarn in darker colors than conventional temperature regulating yarns. However, it is difficult to dye the yarn to the same depth as a yarn made of polyamide alone, especially in a very deep black color, and there are limitations to the use of amino-rich polyamide resin alone. In such a case, by using a resin composition (A) containing carbon black (), it is possible to dye the yarn a very deep black color by making it into a temperature regulating yarn. The more carbon black is kneaded in, the darker the color that can be dyed. However, if the amount is too much, the color cannot be adjusted by dyeing, and the colors that can be expressed are limited. The amount of carbon black kneaded into the resin composition (A) varies depending on the color to be dyed, but is preferably 0.01% by mass or more and 3% by mass or less, and more preferably 0.01% by mass or more and 1% by mass or less, in the resin composition (A).
[0021] The types of olefin resins contained in the resin composition (A) include homopolymers such as polyethylene, polypropylene (hereinafter sometimes referred to as PP), and polymethylpentene (hereinafter sometimes referred to as PMP), as well as copolymers such as ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, ethylene-based ionomers, ethylene-vinyl alcohol copolymers, and ethylene-vinyl chloride copolymers. Polypropylene is particularly suitable as an olefin resin that is highly compatible with crystalline poly-α-olefin, and multiple olefin resins may be used.
[0022] The MFR of the olefin resin is preferably 3 g / 10 min or more and 30 g / 10 min or less. When an alloy resin is formed with a crystalline poly-α-olefin, the viscosity of the resin composition (A) is significantly reduced, making it difficult to form fibers, so that the olefin resin is preferably high in viscosity. Here, MFR is the melt flow rate, and the results are shown as measurements taken at a nozzle diameter of φ1 mm, at 260° C., and under a load of 5 kg.
[0023] The resin composition (A) is preferably produced by melt-kneading a crystalline poly-α-olefin and an olefin resin at a temperature of 240° C. or higher and 280° C. or lower.
[0024] The content of the crystalline poly-α-olefin in the composite fiber of the present invention is preferably 5% by mass or more and 25% by mass or less. If it is 5% by mass or more, temperature control performance is easily achieved, and if it is 25% by mass or less, stable spinning is possible. More preferably, it is 45% by mass or more and 60% by mass or less, and particularly preferably, it is 10% by mass or more and 20% by mass or less.
[0025] The content of the amino-rich polyamide resin in the composite fiber of the present invention is preferably 40% by mass or more and 70% by mass or less. If it is 40% by mass or more, good yarn quality properties are obtained. If it is 70% by mass or less, good temperature control performance is obtained.
[0026] In the composite fiber of the present invention, the fiber cross section may preferably be a core-sheath structure, a sea-island structure, a side-by-side structure, etc. In a fiber in which the resin composition (A) is exposed, the crystalline poly-alpha-olefin may bleed out from the resin composition (A) in an environment higher than the melting point of the crystalline poly-alpha-olefin, so that the cross section structure in which the resin composition (A) is not exposed on the fiber surface is preferred. Particularly preferred fiber cross sections include a core-sheath structure in which the resin composition (A) constitutes the core, or a sea-island structure in which the resin composition (A) constitutes multiple islands. In order to prevent interfacial peeling between the amino-rich nylon resin and the resin composition (A), a more preferred fiber cross section includes a sea-island structure in which the resin composition (A) constitutes 7 or more islands.
[0027] The content of the resin composition (A) in the composite fiber is preferably 30% by mass or more and 80% by mass or less. If the content of the resin composition (A) is 80% by mass or less, the spinnability is good, and if it is 30% by mass or more, excellent temperature control performance is easily exhibited. More preferably, it is 30% by mass or more and 70% by mass or less. Even more preferably, it is 40% by mass or more and 60% by mass or less.
[0028] The amount of terminal amino groups in commonly used polyamide resins is about 30 meq / kg, and the amount of terminal amino groups in the amino-rich polyamide resin used in the composite fiber of the present invention must be at least 60 meq / kg or more. If it is 60 meq / kg or more, it is preferable because a composite fiber with good dyeability can be obtained, and more preferably, it is 70 meq / kg or more, and even more preferably, it is 80 meq / kg or more.
[0029] The conjugate fiber of the present invention can be produced by conjugate spinning the resin composition (A) and an amino-rich polyamide resin. A preferred method for composite spinning of the resin composition (A) and the amino-rich polyamide resin is a melt spinning method in which the resin composition (A) and the amino-rich polyamide resin are melted in an extruder, each resin is discharged from a die while being metered using a gear pump, and then cooled and wound up. The spinning temperature is preferably 160°C or higher and 300°C or lower. Preferred winding methods include a method in which an undrawn yarn is once wound at a low speed of about 400 to 1,200 m / min, and then hot-drawn using a twisting machine to obtain a drawn yarn (conventional method), a method in which a half-drawn yarn is obtained by winding at a high speed of 3,000 to 5,000 m / min (POY method), and a method in which hot-drawing is performed between GR1 and GR2 using a first roller (GR1) of 800 to 1,200 m / min and a second roller (GR2) of about 3,000 to 3,800 m / min to obtain a directly drawn yarn (direct drawing method). The stretching ratio is not particularly limited, but is usually preferably 2 to 4 times.
[0030] The fineness and number of constituent fibers of the conjugated fiber of the present invention are not particularly limited, but for clothing applications, the total fineness is preferably 33 to 150 dtex and the number of constituent fibers is preferably about 12 to 96 f, and more preferably the total fineness is 33 to 84 dtex and the number of constituent fibers is 12 to 48 f.
[0031] The conjugated fiber of the present invention can be used as raw silk as it is, or as false twisted yarn using a false twisting machine, or as a fabric such as a woven or knitted fabric. The fabric such as a woven or knitted fabric can be suitably used for clothing such as general clothing and sportswear, bedding, vehicle interior materials, etc. Suitable examples of the woven and knitted fabrics using the conjugated fiber of the present invention include plain weave, satin weave, and twill weave, as well as plain knit, thermal knit, smooth knit, back pile, and back brushed fabrics. In particular, thermal knit, back pile, and back brushed fabrics are preferred from the viewpoint of exhibiting good dyeability of the conjugated fiber of the present invention.
[0032] When the conjugated fiber of the present invention is used in a woven or knitted fabric, it may be used in a part or the whole of the fabric. When used in a part of the fabric, the specific usage ratio of the conjugated fiber of the present invention is preferably 20% by mass or more, more preferably 35% by mass or more.
[0033] (1) DSC evaluation (melting point, solidification point, heat of fusion, and heat of solidification) The melting point, solidification point, heat of fusion (ΔHm), and heat of solidification (ΔHc) shown below were measured using a differential scanning calorimeter (DSC8500: manufactured by PerkinElmer Japan Co., Ltd.) In the present invention, the measurement using the differential scanning calorimeter was carried out under the following conditions. Sample pan: Al Purge gas: N 2 Temperature range: -50℃~60℃ Heating / cooling rate: 10℃ / min (2) Spinnability evaluation Conjugate spinning was carried out as in the examples and comparative examples. Spinnability was evaluated according to the following criteria. ○: When there is no yarn breakage during 24-hour continuous spinning, or when there is one yarn breakage and the number of defects such as fuzz in the obtained fiber is 2 or less per 1 million meters △: When continuously spinning for 24 hours, except for the above ○, yarn breakage occurs 3 times or less, and the number of defects such as fuzz of the obtained fiber is 5 or less per 1 million meters. ×: When yarn breakage occurs more than 3 times during 24-hour continuous spinning, or when the number of defects such as fuzz in the obtained fiber exceeds 5 per 1 million meters (3) Temperature regulation performance evaluation 1) Fabrication of cylindrical knitted fabric components for evaluating temperature regulation performance The obtained fibers were used to produce a cylindrical knitted fabric with a width of 8 cm using a cylindrical knitting tester (CR-B, 24 gauge, manufactured by Eiko Sangyo Co., Ltd.). The cylindrical knitted fabric was cut into two pieces with a length of 10 cm, and the two pieces were stacked to produce a cylindrical knitted fabric member. A cylindrical knitted fabric member was also obtained in the same manner using the control yarn. 2) Temperature regulation performance evaluation method First, a temperature and humidity sensor was wrapped in a tubular knitted fabric member made of the obtained fiber and a tubular knitted fabric member made of a control yarn. The two tubular knitted fabric members were simultaneously left to stand for 30 minutes in a thermostatic chamber set at 25°C and 30% RH, and then the tubular knitted fabric member was moved to a thermostatic chamber set at 36°C and 70% RH and left to stand for 30 minutes (hereinafter sometimes referred to as "when the temperature is rising"). Furthermore, the two tubular knitted fabric members were simultaneously moved from the thermo-hygrostat set at 36°C and 70% RH to a thermo-hygrostat set at 25°C and 30% RH, and left to stand for 30 minutes (hereinafter sometimes referred to as "when cooling"). During this time, the temperature and humidity sensor measured and recorded the temperature and humidity once every 10 seconds, and the absolute value of the temperature difference between the two tubular knitted fabric components at the same time was defined as the "performance temperature difference," the value at which the "performance temperature difference" was maximum was defined as the "maximum performance temperature difference," and the time from the environmental change until the "performance temperature difference" reached 0°C was defined as the "duration." The larger the "maximum performance temperature difference," the higher the temperature regulation performance, and the longer the "duration," the higher the temperature regulation performance. The temperature regulation performance was evaluated according to the following criteria. ○: Maximum performance temperature difference is 1.0℃ or more and less than 2.0℃ △: Maximum performance temperature difference is 0.5℃ or more and less than 1.0℃ ×: Maximum performance temperature difference is less than 0.5℃ (4) Dyeability evaluation The obtained composite fiber was used to produce a cylindrical knitted fabric with a width of 8 cm using a cylindrical knitting tester (CR-B, 24 gauge, manufactured by Eiko Sangyo Co., Ltd.). The obtained cylindrical knitted fabric was scoured at 70°C, and then dyed at 98°C using a blue acid dye and a black acid dye. * Value and a * Value and b * The color value was measured. A cylindrical knitted fabric prepared in the same manner as the control yarn was dyed, and the L value of the cylindrical knitted fabric after dyeing was * Value and a * Value and b * The color difference (ΔE*) between the tubular knit fabric made of 100% temperature regulating yarn and the tubular knit fabric made of control yarn (nylon only yarn) was calculated, and the dyeability was evaluated from the calculated color difference. The smaller the color difference, the better the dyeability. Therefore, the dyeability was evaluated according to the following criteria. ◎: ΔE* is 0.0 or more and less than 1.0 ○: ΔE* is 1.0 or more and less than 2.0 △: ΔE* is 2.0 or more and less than 5.0 ×: ΔE* is 5.0 or more
[0034] <Crystalline α-polyolefin resin manufacturing example> A heated and dried 10-liter autoclave was charged with 1 liter of 1-hexadecene (C16) and 1 liter of 1-octadecene (C18) as polymerization raw materials and 2 liters of n-heptane as a reaction solvent, and the temperature was increased to 60°C. After that, 40 mmol of triisobutylaluminum, 40 μmol of (1,2'-dimethylsilylene)(2,1'-dimethylsilylene)bis(3-trimethylsilylmethylindenyl)zirconium dichloride, and 40 mmol of methylaluminoxane were added as catalysts, and ethylene and hydrogen were continuously fed to carry out a copolymerization reaction at 0.05 MPa for 2 hours. After the copolymerization reaction was completed, the reaction product was precipitated with acetone and then dried under heating and reduced pressure to obtain 920 g of a crystalline α-polyolefin resin. The copolymer was analyzed by DSC to find that its melting point Tm was 33°C, its heat of fusion ΔH was 67 J / g, its solidification point Tc' was 25°C, and its heat of solidification was 66 J / g. The resulting crystalline α-polyolefin was named CPAO33.
[0035] <Resin composition manufacturing example 1> The CPAO33 prepared by the above method was added to a twin-screw extruder at 4.0 kg / hr, while polypropylene (Novatec (registered trademark) SA01A (grade name) MFR: 11 g / 10 min, manufactured by Nippon Polypropylene) was fed to the twin-screw extruder at 16.0 kg / hr by a feeder, and melt-kneaded at 260° C. The cord-like molten product was water-cooled and pelletized by a pelletizer to obtain a resin composition (A-1). When the resin composition (A-1) obtained here was measured using a differential scanning calorimeter, the melting point of CPAO33 contained in resin composition (A-1) was 29.7°C, the freezing point was 24.3°C, the heat of fusion (ΔHm) of resin composition (A-1) was 11.8 J / g, and the heat of solidification (ΔHc) of resin composition (A-1) was 12.0 J / g.
[0036] <Resin composition manufacturing example 2> While CPAO33 was added to the twin-screw extruder at 4.0 kg / hr, a blend chip of polymethylpentene (Mitsui Chemicals TPX (registered trademark) DX820 (grade name) MFR: 180 g / 10 min) and polypropylene mixed at a mass ratio of 1:7 was fed to the twin-screw extruder at 16.0 kg / hr by a feeder and melt-kneaded at 260° C. The cord-like melt was water-cooled and pelletized by a pelletizer to obtain a resin composition (A-2).
[0037] <Resin composition manufacturing example 3> While CPAO33 was added to the twin-screw extruder at 4.0 kg / hr, a blend chip of polymethylpentene, polypropylene, and a polypropylene-based masterbatch containing 30 mass% of carbon black (manufactured by DIC, hereinafter sometimes referred to as black MB) mixed in a mass ratio of 1:6.9:0.1 was fed to the twin-screw extruder at 16.0 kg / hr by a feeder and melt-kneaded at 260° C. The cord-like melt was water-cooled and pelletized by a pelletizer to obtain a resin composition (A-3) containing 0.3 mass% of carbon black.
[0038] <Resin composition manufacturing example 4> The mass ratio of the blend chips of polymethylpentene, polypropylene, and black MB was changed to 1:6.8:0.2, and a resin composition (A-4) containing 0.6 mass% of carbon black was obtained using the same prototype method as in Resin Composition Production Example 3.
[0039] <Resin composition manufacturing example 5> The mass ratio of the blend chips of polymethylpentene, polypropylene, and black MB was changed to 1:6.95:0.05, and a resin composition (A-5) containing 0.15 mass % of carbon black was obtained using the same prototype method as in Resin Composition Production Example 3.
[0040] Example 1 The resin composition (A-1) and amino-rich polyamide 6 (manufactured by Ube Industries, 1013A (grade name), terminal amino group amount: 94 meq / kg) were used as spinning materials and composite spinning was performed at a temperature of 250°C using an extruder-type composite spinning machine. The resin composition (A-1) was melted separately to form the core and the amino-rich polyamide 6 was melted separately to form the sheath, and then spun from a core-sheath type spinneret at a temperature of 250°C, cooled, oiled, and wound up at a spinning speed of 800m / min. The fiber was then hot-drawn 3.3 times at 80°C using a drawing machine, and heat-set at 150°C using a plate heater to obtain a core-sheath type composite fiber, which is a drawn yarn of 78dtex / 24f. The core-sheath ratio of this core-sheath type composite fiber was 50:50 (mass ratio). The obtained composite fiber was measured using a differential scanning calorimeter, and the heat of fusion (ΔHm) was 5.8J / g, and the heat of solidification (ΔHc) was 5.2J / g.
[0041] Example 2 Except for using the resin composition (A-2), the same spinning materials and spinning conditions as in Example 1 were used to obtain core-sheath type composite fibers.
[0042] Example 3 Except for using the resin composition (A-3), the same spinning materials and spinning conditions as in Example 1 were used to obtain core-sheath type composite fibers.
[0043] Example 4 Except for using the resin composition (A-4), the same spinning materials and spinning conditions as in Example 1 were used to obtain core-sheath type composite fibers.
[0044] Example 5 Except for using the resin composition (A-5), the same spinning materials and spinning conditions as in Example 1 were used to obtain core-sheath type composite fibers.
[0045] Example 6 A core-sheath type composite fiber was obtained by spinning using the same spinning materials and under the same spinning conditions as in Example 1, except that the amino-rich polyamide 6 was a resin (terminal amino group amount: 64 meq / kg) (hereinafter referred to as mixed polyamide 6) prepared by mixing amino-rich polyamide 6 and polyamide 6 (manufactured by Ube Industries, 1013B (grade name), terminal amino group amount: 34 meq / kg) in a 1:1 (mass ratio) (hereinafter referred to as mixed polyamide 6).
[0046] Example 7 A core-sheath type composite fiber was obtained by spinning using the same spinning materials and under the same spinning conditions as in Example 1, except that the amino-rich polyamide 6 was replaced with a mixed polyamide 6 and the resin composition was (A-2).
[0047] Example 8 A core-sheath type composite fiber was obtained by spinning using the same spinning materials and under the same spinning conditions as in Example 1, except that the amino-rich polyamide 6 was replaced with a mixed polyamide 6 and the resin composition was (A-3).
[0048] Example 9 A core-sheath type composite fiber was obtained by spinning using the same spinning materials and under the same spinning conditions as in Example 1, except that the amino-rich polyamide 6 was replaced with a mixed polyamide 6 and the resin composition was (A-4).
[0049] Example 10 A core-sheath type composite fiber was obtained by spinning using the same spinning materials and under the same spinning conditions as in Example 1, except that the amino-rich polyamide 6 was replaced with a mixed polyamide 6 and the resin composition was (A-5).
[0050] Comparative Example 1 Except for using the same polyamide 6 as in Example 6 as the amino-rich polyamide 6, the same spinning materials and spinning conditions as in Example 1 were used to spin a sheath-core composite fiber.
[0051] Comparative Example 2 Except for changing the amino-rich polyamide 6 to the polyamide 6 used in Example 6 and changing the resin composition to (A-2), the same spinning materials and spinning conditions were used as in Example 1 to obtain a core-sheath type composite fiber.
[0052] Comparative Example 3 Except for changing the amino-rich polyamide 6 to the polyamide 6 used in Example 6 and changing the resin composition to (A-3), the same spinning materials and spinning conditions were used as in Example 1 to obtain a core-sheath type composite fiber.
[0053] Comparative Example 4 Except for changing the amino-rich polyamide 6 to the polyamide 6 used in Example 6 and changing the resin composition to (A-4), the same spinning materials and spinning conditions as in Example 1 were used to spin a core-sheath type composite fiber.
[0054] Comparative Example 5 Except for changing the amino-rich polyamide 6 to the polyamide 6 used in Example 6 and changing the resin composition to (A-5), the same spinning materials and spinning conditions were used as in Example 1 to obtain a core-sheath type composite fiber.
[0055] Comparative Example 6 An attempt was made to spin the yarn using only CPAO33 as the core material, but because the difference in viscosity between it and polyamide 6 was too large, the CPAO33 and polyamide 6 separated near the spinneret, making it impossible to form a core-sheath composite yarn.
[0056] Comparative Example 7 A core-sheath type composite fiber was obtained in the same manner as in Example 1, except that the core-sheath ratio (mass ratio) was 20:80 and the resin of the sheath portion was the polyamide 6 used in Example 6. Since the ratio of polyamide 6 was high, the dyeability was good, but since the ratio of CPAO33 was low, the temperature control performance was poor.
[0057] Comparative Example 8 The polyamide 6 of Example 6 was melted and then spun from a single-type spinneret at a temperature of 250°C, cooled, oiled and wound up at a spinning speed of 800m / min. It was then hot-drawn 3.0 times at 80°C using a drawing machine and heat-set at 150°C using a plate heater to obtain a nylon 6 single fiber that is a drawn yarn of 78dtex / 24f. The obtained fiber was used as a control yarn. When this was evaluated by DSC using a differential scanning calorimeter, no melting point peak or solidification point peak was observed in the range of 20°C to 40°C.
[0058] The spinning conditions, spinnability evaluation, temperature control performance evaluation, and dyeability evaluation results for the fibers obtained from Examples 1 to 10 and Comparative Examples 1 to 8 are shown in the following Table 1. CB in the table stands for carbon black.
[0059] [Table 1]
[0060] From the above results, the fibers obtained from Examples 1 to 10 had good spinnability and temperature control performance. The fibers obtained from Examples 1, 2, 6, and 7 had better dyeability than Comparative Examples 1 and 2, so it was confirmed that the use of amino-rich polyamide 6 improves the dyeability, but the dyeability of the black dye was not as sufficient as Comparative Example 8. The fibers obtained from Examples 3 to 5 had better dyeability than Examples 1 and 2 and Comparative Examples 3 to 5, and the dyeability was improved to a level almost equivalent to that of Comparative Example 8. The fibers obtained from Examples 4 and 9 and Comparative Example 4 could be dyed in a deep black color, but the amount of carbon black kneaded in was too high, so there was a limit to the adjustment during dyeing, and they could not be dyed in a vivid blue color. It was found that a fiber using amino-rich polyamide 6 and about 0.6% by mass of carbon black (Example 4) was suitable for black dyeing, and a fiber using amino-rich polyamide 6 and about 0.15% by mass of carbon black (Example 5) was suitable for blue dyeing. From the above, it can be seen that the use of amino-rich polyamide 6 and carbon black is extremely effective when dyeing deep black, and that the use of amino-rich polyamide 6 can solve the problem of being unable to dye deep black when dyeing other colors. [Industrial Applicability]
[0061] The conjugated fiber of the present invention and the fabric made thereof are suitable for use in clothing such as general clothing and sportswear, bedding, and vehicle interior materials.
Claims
1. A composite fiber comprising a crystalline poly-α-olefin having a structural unit constituted by ethylene and a structural unit represented by formula 1, and a polyamide resin having a terminal amino group amount of 60 meq / kg or more. 【Chemistry 1】 (In the formula, the side chain portion R is a linear alkyl group having 9 to 30 carbon atoms.)
2. 2. The core-sheath type composite fiber according to claim 1, wherein the resin composition containing the crystalline poly-α-olefin contains carbon black.
3. The composite fiber according to claim 1 or 2, characterized in that the content of crystalline poly-α-olefin is 5% by mass or more and 25% by mass or less, and the content of polyamide resin having a terminal amino group amount of 60 meq / kg or more is 40% by mass or more and 70% by mass or less.
4. The composite fiber according to any one of claims 1 to 3, wherein the crystalline poly-α-olefin has a melting point of 20°C or more and 50°C or less, a solidification point of 15°C or more and 45°C or less, a heat of fusion (ΔHm) of 60 J / g or more and 100 J / g or less, and a heat of solidification (ΔHc) of 60 J / g or more and 100 J / g or less.
5. 5. The core-sheath type composite fiber according to claim 1, wherein the resin composition containing the crystalline poly-α-olefin forms the core, and the polyamide resin having a terminal amino group amount of 60 meq / kg or more forms the sheath.
6. A fabric comprising the composite fiber according to any one of claims 1 to 5.
Citation Information
Patent Citations
Polypropylene composition
JP1992331248A
Sheath-core composite cross section fiber excellent in moisture absorbing and releasing performance
JP2016196709A
Composite fiber and fabric including the same
JP2019183288A
Fiber excellent in heat stability
JP1989085374A
Endothermic and exothermic conjugate fiber
JP1996311716A